MENTAL HEALTH IN THE PANDEMIC TIMES - FRĄCKOWIAK-SOCHAŃSKA, MONIKA (Society Register, 2020)
The primary aim of this paper is an attempt at the analysis of the prospective direct and indirect, short- and long-term consequences of COVID-19 pandemic for the individuals’ mental health. The secondary aim is to deconstruct the binarity of categories of “mental health” and “mental disorder” in the context of the global critical situation. The pandemic and its consequences such as isolation requirements as well as uncertainty in diverse aspects of life burden the individuals with the stress that results in the increase of anxiety and depressiveness, which challenges the public mental health care systems. Since the anxiety and depressive states are the reactions to a hazardous outside situation, the categories of “mental health” and “mental disorder” needs reconsideration. The theoretical framework of present analyses is determined by the theory of social (cultural) trauma. The method used for the present study is a meta-analysis of theoretical literature, the results of empirical research on COVID-19 pandemic published so far (mostly in medical journals), studies on psychosocial aspects of the previous pandemics (SARS and Ebola), and press publications selected on the basis of their content on mental health issues in the context of the coronavirus pandemic.